SEASONAL DYNAMICS IN DISSOLVED ORGANIC CARBON CONCENTRATIONS IN A COASTAL WATER-TABLE AQUIFER AT THE FOREST-MARSH INTERFACE - Goni M.A.; Gardner I.R. (My University, 2003)
The seasonal dynamics of dissolved organic carbon (DOC) in a subterranean estuary were examined in a coastal water-table aquifer extending across a forest-marsh interface into an adjacent tidal creek that leads to North Inlet (SC). The aquifer is characterized by groundwater flow from the forest recharge area towards the creek. DOC concentrations range from 50 to 140 mg L-1 in the shallow portions of the aquifer below the forest and undergo seasonal changes that are inversely related to temperature and precipitation conditions. Markedly lower DOC concentrations (<10 mg l-1) in the deep portion of the aquifer are consistent with the loss of a large fraction of the original DOC along the groundwater flow paths. Mass balance estimates indicate that over 60% of the DOC losses are due to sorption reactions whereas the rest appear to be caused by heterotrophic decay. Groundwater DOC discharge from the forest, which occurs in a restricted zone of the high marsh, is 5.5 mg carbon m-2 d-1 and accounts for a minor component of the annual carbon export from North Inlet. In contrast, moderately saline (2-12 ppt) ground waters below the marsh display elevated DOC concentrations (~20 mg L-1) that appear to be the result of mixing of fresh ground waters and surface seawater during tidal seepage and concentration during evapotranspiration. The flux of DOC associated with the discharge of these saline ground waters is 600 mg carbon m-2 d-1, which represents a significant fraction of the annual DOC budget for North Inlet.
Keywords: DISSOLVED ORGANIC CARBON; COASTAL AQUIFER; SUBTERRANEAN ESTUARY; GROUND WATER